Pharmacokinetic interaction between SHR2554 and fluconazole: A single-center, open-label and one-sequence crossover phase I trial in healthy Chinese subjects - Dai, Yuyang; Hu, Minwan; Guo, Shaojie; Wu, Feng; Han, Ying; Ni, Siyang; Li, Shaorong; Zhu, Zhenyu; Yuan, Weilan; Zhao, Xiuli (European journal of pharmaceutical sciences, 2025)
SHR2554, a highly selective oral EZH2 inhibitor, shows promise in treating hematologic malignancies. However, its metabolism via CYP3A4 raises concerns about drug-drug interactions. This study evaluates the impact of fluconazole, a moderate CYP3A4 inhibitor, on the pharmacokinetics and safety implications of SHR2554. We conducted a single-center, open-label, single-dose, single-sequence crossover phase I trial. 18 Chinese healthy subjects were orally administered SHR2554 100 mg on Day 1, fluconazole 400 mg on Day 4 and 200 mg QD from Days 5 to 6. SHR2554 100 mg co-administrated with fluconazole 200 mg on Day 7, and fluconazole 200 mg QD from Days 8 to 9. Pharmacokinetic parameters were compared after subjects were administered SHR2554 alone and in combination with fluconazole. Cmax, AUC0-t, and AUC0-∞ were significantly increased when SHR2554 was co-administered with fluconazole. The co-administration led to a 3.29-, 4.79-, and 4.13-fold increase in Cmax, AUC0-t, and AUC0-∞, respectively. Safety evaluations indicated that the observed treatment-emergent adverse events were mild and transient. These findings underline the necessity of caution when co-administered SHR2554 with moderate CYP3A4 inhibitors in clinical settings, providing crucial insights for optimizing future clinical trials. [Display omitted]